Catalytic Asymmetric Synthesis and Stereochemical Revision of (+)-Cryptoconcatone H - Della Felice, Franco (2017)
The total synthesis and structural revision of (+)-cryptoconcatone H are described. Guided by computational studies for the final structure assignment, the stereogenic centers at the tetrahydropyran moiety of (+)-cryptoconcatone H were assembled through catalytic asymmetric methodologies: Krische allylation, cross-metathesis reaction, and THP formation via Pd(II)-catalyzed cyclization. Finally, a Krische allylation reaction established the last stereocenter, and the lactone moiety was formed by ring-closing metathesis.